Neostylidium, a new generic replacement name for Stylidium Dall 1907 (Gastropoda: Caenogastropoda: Cerithiidae) non Eichwald 1855 (Anthozoa) - Doweld, Alexander B. (Zootaxa, 2013)
The genus Stylidium (type species Turritella eschrichtii Middendorff, 1849, by original designation) was established by Dall (in Bartsch, 1907: 178) for a distinctive group of the gastropods in the Bittiinae (Cerithiidae) and remains in current active use (Houbrick, 1993; Bouchet & Rosenberg, 2013). However, the generic name Stylidium Eichwald (1855: 3) was established for a fossil coral prior to the mollusk generic name, which becomes a preoccupied junior homonym.